1997
DOI: 10.1002/(sici)1096-9098(199710)66:2<114::aid-jso8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical adjuvant cryosurgery with antifreeze proteins

Abstract: Background and Objectives Imaging monitored cryosurgery is emerging as an important minimally invasive surgical technique for treatment of cancer. Although imaging allows excellent control over the process of freezing itself, recent studies show that at high subzero temperatures cells survive freezing. Antifreeze proteins (AFP) are chemical compounds that modify ice crystals to needle‐like shapes that can destroy cells in cellular suspensions. The goal of this study was to determine whether these antifreeze pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…apoptosis versus necrosis), cell-based healing responses after freezing/thawing including cell proliferation and migration, and quantitative assessment of ECM structural damage due to freezing. Moreover, the developed model system can be a very useful tool for testing various cryoadjuvants like anti-freeze protein, 16 5-fluorouracil, 7 bleomycin, 20 eutectic forming solutes, 10,11 TNF-alpha 6 which can enhance cryoinjury within a cryolesion and improve the efficacy of cryosurgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…apoptosis versus necrosis), cell-based healing responses after freezing/thawing including cell proliferation and migration, and quantitative assessment of ECM structural damage due to freezing. Moreover, the developed model system can be a very useful tool for testing various cryoadjuvants like anti-freeze protein, 16 5-fluorouracil, 7 bleomycin, 20 eutectic forming solutes, 10,11 TNF-alpha 6 which can enhance cryoinjury within a cryolesion and improve the efficacy of cryosurgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…Dye uptake analyses were performed after thermal treatment, as described by Koushafar et al 26 ; however, injury was assessed after 3, 24 and 72 h of culture using the method outlined in Rupp et al 27 . In brief, the tumour slices were incubated for 30 min in 1 ml of Dulbecco's phosphate-buffered saline (Invitrogen; Gaithersburg, MD) with 9 mM Hoechst 33342 (Sigma) and 16 mM EthD-1 (Molecular Probes; Eugene, OR).…”
Section: Dye Uptakementioning
confidence: 99%
“…AFPs at a very high concentration (>5 mg/ml) have been shown to modify ice crystals to a spicular shape (reducing dendrite tip diameter) such that mechanical disruption of the membranes and tissue connective structures is achieved [43, 44, 82, 83]. Pham et al, showed in an in vivo prostate cancer model that the presence of AFPs can cause injury at temperatures up to −5°C [44].…”
Section: Adjuvants With Cryosurgerymentioning
confidence: 99%